Molecular detection of isoniazid monoresistance improves tuberculosis treatment: A retrospective cohort in France. Issue 1 (July 2022) - Bachir, Marwa; Guglielmetti, Lorenzo; Tunesi, Simone; Billard-Pomares, Typhaine; Chiesi, Sheila; Jaffré, Jérémy; Langris, Hugo; Pourcher, Valérie; Schramm, Frédéric; Lemaître, Nadine; Robert, Jérôme; ,
Highlights: Less than 25% of isoniazid-resistant-TB are diagnosed at an early stage in France. Early diagnosis of isoniazid resistance shortens time to adequate treatment. Adequate treatment of isoniazid-resistant-TB improves treatment outcome. Summary: Objectives: Isoniazid-monoresistant tuberculosis (HR-TB) requires early diagnosis and adapted treatment to achieve optimal outcomes. The primary aim of the study was to assess the impact of the implementation of rapid diagnostic tests on HR-TB treatment in France. Methods: We designed a retrospective multicentre study including consecutive HR-TB patients diagnosed in 2016 and 2017. Implementation of a molecular assay detecting isoniazid resistance directly on a clinical sample was recorded. The association between early implementation of such assays and adequate treatment was assessed by a multivariable Cox proportional hazards model. Results: Overall, 99 HR-TB patients were included from 20 University Hospitals. Among all smear-positive HR-TB patients, only 26% beneficiated from early molecular HR detection. This detection was independently associated with shorter time to adequate treatment (HR = 2.0 [1.1–3.8], p = 0.03). Conclusion: In our study, molecular detection of HR on an initial sample was independently associated with earlier treatment adaptation.